Pro-Environmental Behaviour in Indonesia: What Don’t We Recognize? - Dudi Permana; Fellita Irmadela Farandy; Hasliza Abdul Halim (Management Institute Faculty of Economics Universitas Andalas, 2023)
Global warming and increasing environmental pollution are caused by human behaviour These facts have driven consumer to change their behaviour to become more environment-friendly. This study aims to analyze how psychological factor, namely green appearance consciousness (X1), environmental consciousness (X2), and green-self identity (X3) influence pro-environmental behaviour (Y). This research belongs to causal associations research. The data were obtained from 130 people, who implemented zero-waste lifestyle. In this study we used Partial Least Square analysis method to measure relationship between variables. The result shows that green appearance consciousness (X1) and environmental consciousness (X2) have significant influences to pro-environmental, while green self-identity (X3) does not have significant influences to pro-environmental behaviour (Y).